STUDI KUALITATIF PENGALAMAN IBU DROP OUT ALAT KONTRASEPSI DI MASA PANDEMI COVID-19 - Anggriani, Yunita (Jurnal Ilmu Kebidanan, 2024)
Background: The COVID-19 pandemic has caused disruptions in the health care system, particularly in reproductive health services that focus on family planning services. The emergence of the policy of limiting social behavior and physical distancing has led to behavioral changes in female family planning acceptors during the pandemic. The disruption of the family planning service system has caused an increase in the incidence of drop out of contraceptives during the COVID-19 pandemic. The purpose of this research to identify about the experience and reasons for mothers to drop out of contraceptives during the COVID-19 pandemic. This method of research is qualitative research used a phenomenological approach. Result: The experience of mothers dropping out of contraceptives during the COVID-19 pandemic varied, and the reasons for mothers to drop out of contraceptives included being worried and afraid of contracting COVID-19, low knowledge of mothers about contraceptives. Conclusion: Feelings of worry and fear of contracting COVID-19 are the main reasons for mothers to drop out of contraceptives during the COVID-19 pandemic. Therefore, providing comprehensive family planning services and monitoring for repeat visits to family planning acceptors are the main focus and special attention.